Civil disobedience and conscientious objection. (December 2016) - Cooke, Maeve; Petherbridge, Danielle
The question of civil disobedience has preoccupied philosophical discourse at least since Thoreau's articulation of disobedience as a form of non-compliance and Rawls' classic definition outlined in the wake of the civil rights and student protest movements of the 1960s. It has become increasingly clear, however, that these classic definitions are being challenged and rethought from a variety of traditions in the wake of contemporary protests. These articles engage with the most recent debates surrounding civil disobedience and conscientious objection, opening up original new paths for thinking about forms of protest. They also reveal disagreements about how to understand civil disobedience and about the place of conscience in political protest, inviting further discussion on these questions and issues.